Expression of the botulinum neurotoxin serotype D binding domain in Brevibacillus brevis and its evaluation as a candidate vaccine antigen in mice - Theron, Jacques (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2006.